Sambung Pucuk Dini Pada 5 Jenis Klon Kakao (Theobroma cacao L.) Dengan Umur Batang Bawah Yang Berbeda - Ridwan Ridwan; Bahrudin Bahrudin; Sakka Samudin (Universitas Tadulako, 2015)
The aimed of this research were to determined the suitable of rootstock age for each cacao clone on the early grafting technique, to determined the best of cacao clone with great succesfull on early grafting technique and to obtain the best rootstock age for early grafting technique. The research was conducted during period of January to April 2015 at Laboratory of Forestry Sciences, Forestry Faculty, Tadulako University. This research was arranged based on completely randomized design with factorial treatments. The treatments consists of two factors, the first was superior cocoa clones as the entries and the second was the various age of rootstock. The output data was analyzed by Analysis of Varian and Duncan Multiple Range Test at 5%. The result showed that the suitable of rootstock age for each clone on the early grafting of cacao plant was not presented. Clone M01 had the best growth response in all observed variable. The average growing speed were 10,44 days after grafting. The percentage of success grafting was 100%, the number of shoots were 6,22, the number of leaves were 11,33 leaves, and shoot diameter was 0,40 mm. The two weeks-rootstock reflected better responses in all observed variable, where the average growing speed was 10,40 days after grafting, the percentage of living graft was 100%, the number of shoot was 5,20, the number of leaves was 10,67 leaves and shoot diameter was 0,33 mm.